Capacitación a los empleados de la empresa midispro de la ciudad de Babahoyo en la provincia de Los Ríos en el año 2023. - Sobenis Flor, Junior Ismael (2025)
This work was carried out with the objective of determining how Training and Development affect the performance of Human Talent in the MIDISPRO company in the city of Babahoyo in the Province of Los Ríos in the year 2023. The population and study sample consisted of 15 employees and administrators who work in the different work areas. The technique used for data collection was the survey, which was made up of a 12-item questionnaire for the two variables, designed using the Likert scale with 4 levels of responses. The Training and Development variable was made up of 6 items, as was the Human Talent Performance variable, in both cases with 4 categories and dimensions for each of them. The study was based on the quantitative approach, of non-experimental design. To test the hypothesis, the normality of the variables was determined by the Kolmogórov-Smirnov test, obtaining that both variables do not follow a normal distribution. It is concluded that employees must satisfy certain basic and fundamental needs in order to achieve the desired goal, so the company must place emphasis on the application and evaluation of strategies that lead to improving the motivation and organizational climate of employees to take the growth of the company to higher levels.